EMPIRICAL STUDY OF INFLUENCE OF FINANCIAL INNOVATION ON ORGANISATIONAL PERFORMANCE OF SELECTED NIGERIAN INSURANCE COMPANIES - Oloruntoba Oyedele (Malete Journal of Accounting and Finance)
Despite the proliferation of information technology, many Nigerian insurers do not deploy fully integrated computer software system. This study therefore examines the effect of financial innovation on organisational performance with specific reference to the Nigerian insurance industry. Specifically, the study examines the association that exists between process innovation, product innovation, service innovation, organisation innovation and organisational performance. A survey research approach was adopted to sample the opinion of respondents. A purposive sample technique was adopted to select 150 senior managers of the selected 69 insurance companies in Southwest, Nigeria. The data collection instruments for the study were structured questionnaires designed for the study. Path Analysis was used to analyse the data. The study concluded that process innovation, product innovation, service innovation, and organisation innovation have positive and significant association with organisational performance. Therefore, the study recommended that it is imperative for the insurance sector in Nigeria to fully implement financial innovation to enable it achieve its vision of being the industry of choice among emerging markets noted for high market capacity, transparency, efficiency and safety and to attain the position of one of the 20 largest insurance markets in the world by the year 2030.